Robert Price Higgins―Aspects of his life and his contributions to meiobenthic research (1932–2022) - Neuhaus, Birger; Pardos, Fernando; Storch, Volker; Kristensen, Reinhardt M. (Zootaxa, 2023)
The scientific life of Robert P. Higgins was devoted to meiofauna, microscopically small animals living in aquatic sediments from the intertidal to hadal depths worldwide. He focused on the taxonomy, life-history, and ecology of the marine taxa Kinorhyncha, Tardigrada, and Priapulida and co-discovered the phylum Loricifera. He improved the methods for studying meiofauna and contributed significantly to spreading knowledge about these animals. Aspects of his life are described and lists of his publications, taxa described, contributions to science, and honours received are provided.